2022
DOI: 10.23960/mtk/v10i2.pp196-207
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Self Confidence Terhadap Kemampuan Pemecahan Masalah Matematis Siswa

Abstract: This research aims to determine the effect of self confidence on student’s mathematical problem solving abilities. The population in this research was all seventh grade students of SMP Swadhipa 1 Natar in the odd semester of the 2021/2022 academic year which were distributed in three classes, namely grades VIIA, VIIB and VIIC. The samples of this research were students of class VIIB and class VIIC who were selected by cluster random sampling technique with a total of 50 students. Research data taken in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
2
7
0
3
Order By: Relevance
“…This research is important to carry out to improve mathematical problem-solving skills, as an effort to fulfill one of the important skills of the 21st century. Discovery learning integrated modules can support the implementation of discovery learning in improving mathematical problemsolving (Septiani et al, 2018;Septiyan et al, 2020). Based on the results of the research, it shows that the discovery learning model assisted by the mathematics learning module can improve students' mathematical problem-solving skills.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This research is important to carry out to improve mathematical problem-solving skills, as an effort to fulfill one of the important skills of the 21st century. Discovery learning integrated modules can support the implementation of discovery learning in improving mathematical problemsolving (Septiani et al, 2018;Septiyan et al, 2020). Based on the results of the research, it shows that the discovery learning model assisted by the mathematics learning module can improve students' mathematical problem-solving skills.…”
Section: Discussionmentioning
confidence: 94%
“…Based on research conducted showed that the discovery learning model was not effective in improving students' mathematical problem-solving skills (Diana et al, 2016;Putri et al, 2017;Septiani et al, 2018). However, research conducted by other researchs shows that the discovery learning model is effective in improving students' mathematical problem-solving skills (Anggreini et al, 2018;Hanum et al, 2019;Jana & Fahmawati, 2020). Based on the facts from the research results, it can be concluded that there are gaps in some of the previous research results .…”
Section: Abstract 1 Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…With this experience understudies utilize their insight to apply to tackling issues experienced during the growing experience. This is as per Melani's viewpoint (Masniari, Tini Yunarti, 2014) the drawn out objective of learning arithmetic is to investigate understudies' capacities so they can foster themselves and have the option to take care of issues that emerge. Critical thinking is viewed as a vital part since critical thinking can further develop understudies' reasoning abilities and capacities which are accepted to be adaptable or utilized by these understudies while managing issues in regular day to day existence.…”
Section: Introductionmentioning
confidence: 99%
“…The trouble experienced by understudies in tackling numerical issues is the absence of significance of the material got so understudies find it challenging to expand on the information acquired (Masniari, Tini Yunarti, 2014) . For this situation exercises should be planned that include understudies effectively in deciphering a topic so that learning can be handily acknowledged by understudies.…”
Section: Introductionmentioning
confidence: 99%